CORRELATION BETWEEN PARENTAL ATTENTION AND MATHEMATICS LEARNING OUTCOMES TO FIFTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN PREMBUN SUB-DISTRICT IN ACADEMIC YEAR OF 2020/2021 - Dian Candra Wati; Ngatman Ngatman; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The study aimed to determine the positive and significant correlation between parental attention and mathematics learning outcomes to fifth grade students of public elementary schools in Prembun Sub-district in academic year of 2020/2021 and to determine the contribution of parental attention on mathematics learning outcomes. It was bivariate correlational quantitative research. The sampling method was probability sampling technique. Data analysis used correlation test and adjusted R square with a significance level of 0.05. The correlation test was sig=0.000 (Sig < 0.05). It indicated that there was positive and significant correlation between parental attention and student’s mathematics learning outcomes. It meant that having much parental attention, the higher student's mathematics learning outcomes and vice versa. The parental attention contributed 16.40% to mathematics learning outcomes and the remaining 83.60% is influenced by other factors.Keywords: parental attention, mathematics learning outcomes